Effect of rapid weight loss on physical performance in judo athletes: is rapid weight loss a help for judokas with weight problems? - Fortes, L. S.; Costa, B. D. V.; Paes, P. P.; Cyrino, E. S.; Vianna, J. M.; Franchini, E. (International Journal of Performance Analysis in Sport, 2017)
The goal of the present study was to analyse the impact of rapid weight loss methods (10%) on physical performance of judo athletes. Thirty-nine adult male judo athletes were selected to participate in the present study. Athletes were randomly allocated in two groups: experimental (EG, n = 20) and control (CG, n = 19). Twenty-four hours before the beginning of experimental approach, athletes were submitted to anthropometrical measurements and performed the Special Judo Fitness Test. The weight loss in the EG was conducted to generate a mean loss of 5% per week during 2 weeks. A two-way analysis of variance with repeated measurements was conducted to compare groups and moments. There was a group and moment interaction (p = .001) for body mass, with decrease only for the EG (?% = -10.6%, p = .01). There was also a group and moment for the Special Judo Fitness Test index (p = .001), with an improvement only in the CG (?% = -6%, p = .01). It was concluded that the rapid weight loss process was not a good strategy for judo athletes` performance optimisation.